Gestão ambiental urbana, diferente em cidades planejadas? O caso de três cidades brasileiras - Márcia de Andrade Mathieu; Neli Aparecida de Mello (Confins)
Using the urban environment problematic, the article looks for decoding and comparing the current reality of the environmental problems that takes place into planned cities in Brazil: Brasilia, Palmas and Goiânia. The cities in question had been constructed at different times. Goiania was founded in 1933, Brasilia in 1960 and Palmas in 1989. To each of these times, a particular way to approach the relative questions to the environment was used. The basic question is to know whether the planning produced different urban environments or the consequences seem alike, independently of the type of planning. The diagnosis of the urban environment that will be carried through for each one of the cities, analyzes them as some of the urban services to the environment quality are distributed: the water, solid residues, occurrence of water supply by wells.